Compressive split Hopkinson pressure bar tests with imperfect dimension - Lee, Clive Tzen Liang (Nanyang Technological University, 2022)
When studying mechanical and engineering failure, mechanical properties of materials used in the system are often studied as part of the investigation. How materials behave in a quasi-static environment have been thoroughly studied and information on how they perform are widely shared across the internet and in engineering industries. However, information on how they behave in high strain rate circumstances is scarce in comparison. Knowledge on how they behave in dynamic environments will give us a better understanding of the stress and strain rate which can be crucial in investigating said engineering failures. To study this, the Split Hopkinson Pressure Bar (SHPB) was thus invented to investigate the properties of materials at high strain rates. Depending on configuration, it was able to conduct tests under compression, tension and torsion. With the use of a nitrogen gas gun, the SHPB would utilize strain gauges mounted on its incident and transmission bars to record waves propagated from the impact of the striker bar through the specimen being tested. This report will focus on compressive study of the SHPB, in particular, specimens with imperfections. On top of conducting service and repair of the SHPB, the author recreated experiments of previous students to ensure accuracy of results before conducting investigative study on how certain imperfections affect the maximum strain of the specimens and its relevance to modern day engineering.